2012
DOI: 10.1007/s10548-012-0218-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1 Hz Repetitive Transcranial Magnetic Stimulation Over the Auditory Cortex on Audiometry and Otoacustic Emissions

Abstract: Repetitive transcranial magnetic stimulation (rTMS) at low frequencies (≤1 Hz) delivered to the primary motor cortex for 15 min or longer has been shown to reduce motor cortex excitability. Over the visual cortex, 1 Hz rTMS led to increased phosphene thresholds and over the auditory cortex rTMS reduced auditory evoked potentials. rTMS above the auditory or temporo-parietal cortex has also been reported to reduce the severity of auditory hallucinations and the perception of tinnitus. However, possible unwanted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…While the evidence of an antidepressant effect of TMS is established (Hedge's g = 0.55 in a meta-analysis [ 125 ]) and indeed approved for treatment-resistant depression by the Food and Drug Administration, the evidence for clinical therapeutic effects in other neuropsychiatric disorders and also the effects on specific cognitive functions are still not very strong, requiring more research. The safety profile of TMS is well characterized [ 126 , 127 ]. TDCS, however, has until now been much less investigated in treatment studies (e.g.…”
Section: Cognitive Enhancers In Healthy Peoplementioning
confidence: 99%
“…While the evidence of an antidepressant effect of TMS is established (Hedge's g = 0.55 in a meta-analysis [ 125 ]) and indeed approved for treatment-resistant depression by the Food and Drug Administration, the evidence for clinical therapeutic effects in other neuropsychiatric disorders and also the effects on specific cognitive functions are still not very strong, requiring more research. The safety profile of TMS is well characterized [ 126 , 127 ]. TDCS, however, has until now been much less investigated in treatment studies (e.g.…”
Section: Cognitive Enhancers In Healthy Peoplementioning
confidence: 99%
“…It has been clearly demonstrated that unilateral hearing loss can lead to auditory cortex reorganization 7 33 34 . Evidence of auditory plasticity in mature humans has been obtained from studying individuals with unilateral deafness 35 36 37 38 39 . In individuals with normal hearing, monaural stimulation results in asymmetrical activation of the central auditory system, in which the contralateral hemisphere produce greater activation than the ipsilateral hemisphere, which is referred to as “contralateral dominance” 40 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that these changes in protein expression may contribute to the molecular mechanism underlying the significant physiological changes in ISSHL patients, which lead to acoustic disorders following hearing loss. Li et al demonstrated that a high degree of reorganization was associated with poor recovery from hearing loss in SSHL patients 35 . Thus, we performed rTMS as a new therapy based on the central auditory system remodeling theory.…”
Section: Discussionmentioning
confidence: 99%
“…In line to some extent with the study method of Perrot et al (50), Schönfeldt-Lecuona et al (52) also tested the functional efferent connectivity, although with noninvasive electrical stimulation. Instead of direct electrical stimulation, they used transcranial magnetic stimulation (TMS) on the superior temporal gyrus.…”
Section: The Corticofugal Auditory System In Humansmentioning
confidence: 97%
“…The rationale for treating tinnitus with TMS is the reported hyperactivity in the left primary auditory cortex in tinnitus patients when measured with functional imaging, such as positron emission tomography (57,58; for review, see Lanting et al [59]). With TMS of the auditory cortex, Schönfeldt-Lecuona et al (52) did not find changes in hearing level thresholds or distortionproduct OAEs (DPOAEs) of the tinnitus patients, suggesting that no auditory efferent activity was induced. However, the localized magnetic field might have been too small to stimulate the auditory corticofugal system.…”
Section: The Corticofugal Auditory System In Humansmentioning
confidence: 99%